Comparison of anti-Campylobacter activity of free thymol and thymol-β-d-glucopyranoside in absence or presence of β-glycoside-hydrolysing gut bacteria. (15th April 2015) - Epps, Sharon V.R.; Petrujkić, Branko T.; Sedej, Ivana; Krueger, Nathan A.; Harvey, Roger B.; Beier, Ross C.; Stanton, Thad B.; Phillips, Timothy D.; Anderson, Robin C.; Nisbet, David J.
Highlights: Thymol is an effective bactericide against Campylobacter . Rapid absorption of thymol prevents delivery of thymol to the distal gut. Thymol-β-d -glucopyranoside is resistant to absorption. Thymol-β-d -glucopyranoside is hydrolysed by β-glycosidase-producing gut bacteria. Thymol released from thymol-β-d -glucopyranoside effectively kills Campylobacter . Abstract: Thymol is a natural product that exhibits antimicrobial activity in vitro but in vivo results indicate that absorption within the proximal alimentary tract precludes its delivery to the distal gut. Presently, the anti- Campylobacter activity of thymol was compared against that of thymol-β-d -glucopyranoside, the latter being resistant to absorption. When treated with 1 mM thymol, Campylobacter coli and jejuni were reduced during pure or co-culture with a β-glycoside-hydrolysing Parabacteroides distasonis. Thymol-β-d -glucopyranoside treatment (1 mM) did not reduce C. coli and jejuni during pure culture but did during co-culture with P. distasonis or during mixed culture with porcine or bovine faecal microbes possessing β-glycoside-hydrolysing activity. Fermentation acid production was reduced by thymol-β-d -glucopyranoside treatment, indicating that fermentation was inhibited, which may limit its application to just before harvest. Results suggest that thymol-β-d -glucopyranoside or similar β-glycosides may be able to escape absorption within the proximal gut and become activated by bacterial β-glycosidases in the distal gut.